(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Background Head injury remains a major cause of morbidity and mortality worldwide. While computed tomography (CT) scans serve as a critical diagnostic tool in detecting intracranial lesions, forensic autopsy remains the gold standard for definitive assessment. This study evaluates the diagnostic accuracy of 128-slice CT scans in identifying fatal head injuries by comparing imaging findings with autopsy results. Methods A retrospective observational study was conducted on 60 cases of fatal head injuries admitted to A.J. Institute of Medical Sciences & Research Centre between December 2016 and April 2018. CT scan findings were systematically compared with autopsy results, with a focus on intracranial haemorrhages and contusions. Sensitivity, specificity, and concordance between imaging and post-mortem findings were analyzed using IBM SPSS Statistics (Version 17). Results Among the 60 cases, 90% were males, with road traffic accidents accounting for 86.67% of cases. The sensitivity of CT scans for different types of hemorrhages was as follows: subarachnoid hemorrhage (60.71%), subdural hemorrhage (58%), extradural hemorrhage (40.9%), and intracerebral hemorrhage (11.11%). Contusion detection was highest in the frontal lobe (90.32%) and lowest in the corpus callosum (16.67%). Smaller contusions and posterior cranial fossa lesions were frequently missed on CT scans. Conclusion While CT scans play a valuable role in forensic and clinical assessments, they exhibit limitations in detecting smaller hemorrhages and contusions. The study underscores the need for high-resolution imaging, contrast-enhanced CT, and serial imaging to improve diagnostic accuracy. Future research should focus on MRI integration, AI-assisted imaging, and multicentric studies to enhance forensic radiology.